2021
DOI: 10.3390/ijerph18136907
|View full text |Cite
|
Sign up to set email alerts
|

The Health Status Transition and Medical Expenditure Evaluation of Elderly Population in China

Abstract: (1) Background: Because of the rapid expansion of the aging population in China, their health status transition and future medical expenditure have received increasing attention. This paper analyzes the health transition of the elderly and how their health transition impacts medical expenditures. At the same time, feasible policy suggestions are provided to respond to the rising medical expenditure and the demand for social care. (2) Methods: The data were obtained from the China Health and Retirement Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Family caregivers can provide self-care training for the disabled to ensure their basic living and self-care ability and promote the rehabilitation of the mental, physical, and social functions of people with disabilities ( 59 ). Additionally, the different effects of socioeconomic factors in the different disability groups also indicated that precise, classified, and targeted efforts in health care should be made by considering these different demand-side health needs according to disability types ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Family caregivers can provide self-care training for the disabled to ensure their basic living and self-care ability and promote the rehabilitation of the mental, physical, and social functions of people with disabilities ( 59 ). Additionally, the different effects of socioeconomic factors in the different disability groups also indicated that precise, classified, and targeted efforts in health care should be made by considering these different demand-side health needs according to disability types ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older people are a vulnerable group confronting a higher risk of chronic diseases and declination of health conditions. The health risk of the elderly will cause rising demand for medical services and medical expenditure from 2020–2060 [ 41 ]. With the demographic transition, the aging population poses greater challenges to China’s public health than ever.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study contributes to the literature on care for older people from the view of policy support. Theoretical research on the policy instrument mix in terms of input of care institutions for older people has been paid attention recently ( 2 , 29 ). However, studies focusing on the combined effects of different characteristics of a policy instrument mix are scarce ( 9 , 30 ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…As of November 2020, China recorded 264.02 million people aged over 60, accounting for 18.7% of the total population, and 190.64 million people aged over 65, representing 13.5% of the overall population. Care for older people has become a significant issue affecting social development in China ( 1 , 2 ). With a decline in the birth rate and family care functions, community care and home care have failed to provide older people high-quality care services.…”
Section: Introductionmentioning
confidence: 99%